Manajemen Tourism Information Center di Kabupaten Sidoarjo - Darwanto, Dika Pratama; Maesaroh, Maesaroh - (Journal of Public Policy and Management Review, 2020)
Tourism is important sector in foreign exchange income but it’s diversity is not followed by awareness of the tourist attractions of each region. One of the factors supporting the tourism appeal of region is the establishment of Tourism Information Center. Sidoarjo is the newest destination in East Java because there is a tourism of Sidoarjo Mud. Therefore, Department of Youth, Sport and Tourism Sidoarjo form a Tourism Information Center as an attraction for tourists to visit Sidoarjo. Use of management functions according to Donovan and Jackson assited the theoretical approach from Moenir by looking at inhibitory factors an orgnization such as the Tourism Information Center working method system became a benchmark. So that there are some indicators that are the point of the problem such as staffing indicators namely Tourism Information Center assignments that seem ovelapping, controlling several programs that must be improved make this raised in the research as a description of Tourism Information Center management. Both aspects can be the initial foundation for analyzing whether Tourism Information Center management is running properly. It’s necessary to then be reviewed in the form of a conclusion that there are several factors that hinder of Sidoarjo Tourism Information Center in it’s efforts to help manage tourism. Such as regulations that impede both organizational and performance, synergy with several supporting aspects and optimizing avalaible budgets. The conclusion can be the reference of Tourism Information Center to be more improvement in developing tourim and become a Tourism Information Center.